2016
DOI: 10.17796/1053-4628-40.6.480
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quantitative Assessments of Salivary Ion Activity Product for Hydroxyapatite and Buffering Capacity in Children with Different Caries Experience

Abstract: pH measurement after HCl titration in saliva could be used as chair side screening test for the assessment of caries risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The intervention in preschool children with the daily drinking of milk supplemented with Lactobacillus rhamnosus and Bifidobacteruim longum improved the buffer capacity of saliva in a consistent way, contributing to mitigate this risk factor for the appearance and progression of ECC 2 . No studies were found in preschoolers that compared the salivary buffering capacity after an intervention of milk with probiotics, nevertheless, the advantages of incorporating probiotics into dairy products because of the buffering capacity of the food matrix and the presence of milk components are found in the correlation with tooth enamel remineralization 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intervention in preschool children with the daily drinking of milk supplemented with Lactobacillus rhamnosus and Bifidobacteruim longum improved the buffer capacity of saliva in a consistent way, contributing to mitigate this risk factor for the appearance and progression of ECC 2 . No studies were found in preschoolers that compared the salivary buffering capacity after an intervention of milk with probiotics, nevertheless, the advantages of incorporating probiotics into dairy products because of the buffering capacity of the food matrix and the presence of milk components are found in the correlation with tooth enamel remineralization 30 .…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variables were the changes of S. mutans and Lactobacillus spp. A Mann Whitney U test for numerical variables and X 2 test for categorical variables was performed.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most relevant caries-protective factors in saliva is the buffer capacity, given mainly by bicarbonate (HCO 3 -). The bicarbonate system stands out because when an acid is added to the oral environment, it reacts releasing a weak carbonic acid that rapidly dissociates into water and CO 2 , resulting in a complete elimination and increasing the pH of the oral environment, following the chemical balance: H + + HCO 3 -⇋ H 2 CO 3 ⇋ H 2 O + CO 2 [30]. The phosphate and the protein buffers are also important to enhance the buffer capacity in saliva.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most relevant caries-protective factors in saliva is the buffer capacity, given mainly by bicarbonate (HCO 3 − ). The bicarbonate system stands out because when an acid is added to the oral environment, it reacts releasing a weak carbonic acid that rapidly dissociates into water and CO 2 , resulting in a complete elimination and increasing the pH of the oral environment, following the chemical balance: H + + HCO 3 − ⇋ H 2 CO 3 ⇋ H 2 O + CO 2 [ 7 ]. The phosphate and the protein buffers are also important to enhance the buffer capacity in saliva.…”
Section: Introductionmentioning
confidence: 99%